2015
DOI: 10.1016/j.ijhydene.2015.03.139
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorption by perforated graphene

Abstract: We performed a combined theoretical and experimental study of hydrogen adsorption in graphene systems with defect-induced additional porosity. It is demonstrated that perforation of graphene sheets results in increase of theoretically possible surface areas beyond the limits of ideal defect-free graphene (~2700 m 2 /g) with the values approaching ~5000 m 2 /g. This in turn implies promising hydrogen storage capacities up to 6.5 wt% at 77 K, estimated from classical Grand canonical Monte Carlo simulations. Hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 53 publications
7
41
0
Order By: Relevance
“…In agreement with theory, our recent experiments demonstrated that hydrogen sorption by r-GO and KOH activated r-GO (a-r-GO) follows standard trends and correlates with SSA values (~100-3300 m 2 /g range in our experiments) both at room temperature and 77K. [32][33][34] Nevertheless, reports on extremely high hydrogen uptakes (either in absolute values or relative to reported SSA) by various types of r-GO continue to appear, [35] outnumbering studies which find trivial uptake numbers. [36] In several cases the data presented as an evidence for exceptional hydrogen storage of graphene are represented by abnormal shapes of isotherms [35,37] or obtained by rather uncommon measurement methods.…”
Section: Introductionsupporting
confidence: 91%
“…In agreement with theory, our recent experiments demonstrated that hydrogen sorption by r-GO and KOH activated r-GO (a-r-GO) follows standard trends and correlates with SSA values (~100-3300 m 2 /g range in our experiments) both at room temperature and 77K. [32][33][34] Nevertheless, reports on extremely high hydrogen uptakes (either in absolute values or relative to reported SSA) by various types of r-GO continue to appear, [35] outnumbering studies which find trivial uptake numbers. [36] In several cases the data presented as an evidence for exceptional hydrogen storage of graphene are represented by abnormal shapes of isotherms [35,37] or obtained by rather uncommon measurement methods.…”
Section: Introductionsupporting
confidence: 91%
“…Recent theoretical modelling results demonstrated that SSA values as high as 5000 m 2 /g are possible for graphene sheets perforated with small size holes and packed into 3D structure with optimal inter-layer distance of 0.7-1 nm. 15 However, the experimental realization of ordered structures proposed in ref. 15 is hindered by the absence of suitable methods to hold graphene layers separate from each other.…”
mentioning
confidence: 99%
“…15 However, the experimental realization of ordered structures proposed in ref. 15 is hindered by the absence of suitable methods to hold graphene layers separate from each other.…”
mentioning
confidence: 99%
“…A systematic study of the effects of doping on flexoelectricity is currently in the course graphene at 1-2% at room temperature. Besides the obvious strategy of working at cryogenic temperature, in several theoretical works physical interactions were shown enhanced within nanocavities produced by rippling [58], within multilayers with specific (nanometric) interlayer spacing [59,60] or with nanosized perforations of the sheet [61]. From the methodological point of view, it is interesting to observe that these works address the problem of physisorption combining different methodologies besides DFT (see Table 2), including classical approaches based on empirical Force Fields, different types of dynamical treatment of hydrogen (QM dynamics, Monte Carlo and thermodynamic evaluation of the adsorption).…”
Section: Physisorptionmentioning
confidence: 99%